PENGARUH FINANCIAL DISTRESS, LEVERAGE, CAPITAL INTENSITY TERHADAP PRUDENCE DENGAN MENGGUNAKAN COMPANY SIZE SEBAGAI VARIABEL MODERASI - Susanti, Susanti; Bawono, Andy Dwi Bayu (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study examines the influence of financial distress, leverage, and capital intensity on accounting prudence, using company size as a moderating variable. The sample comprises energy sector companies listed on the Indonesia Stock Exchange (IDX). The total population for this study includes 86 companies listed on the IDX. The analytical techniques employed include multiple linear regression analysis and moderation regression analysis using SPSS 26. The data analysis results indicate that financial distress significantly affects prudence. However, leverage and capital intensity do not show a significant influence on prudence. Furthermore, company size is found to moderate the effects of financial distress, leverage, and capital intensity on prudence among the studied companies. Keywords: Accounting Prudence; Capital Intensity; Company Size; Financial Distress; Leverage